Digital Literacy in Enhancing Collaborative Teaching: A Systematic Review - Wider, Walton; Saad, Abidah; Mahmood, Nor Asiah; Ishak, Suhaida; Aziz, Muhammad Ridzuan Abdul; Wu, Changhe; Wu, Hao; Tanucan, Jem Cloyd M. (International Review of Research in Open and Distributed Learning, 2026)
Digital literacy is central to collaborative teaching in technology-mediated environments, particularly open and distributed learning. Guided by the Community of Inquiry and TPACK (Technological Pedagogical Content Knowledge) frameworks, this systematic review examines how digital literacy enables educators to codesign instruction, sustain interaction, and support reflective practice while addressing structural and contextual barriers. Following PRISMA 2020, comprehensive searches in Scopus and the Web of Science identified 32 peer-reviewed articles published in 2024. Thematic synthesis produced three strands: (a) integration of digital literacy in education, highlighting links to teaching presence, professional development, and instructional design; (b) digital literacy in response to educational challenges, demonstrating its role in resilience, equity, and socio-emotional support across remote and hybrid contexts; and (c) advancing learning through digital competencies, detailing gains in collaboration, critical inquiry, and innovative use of augmented reality, virtual reality, data analytics, and emerging AI tools alongside ethical considerations. Evidence indicates that digital literacy functions as a pedagogical capacity rather than solely a technical skill and yields the strongest outcomes when aligned with institutional culture, curriculum design, and continuous professional learning. Policy recommendations include sustained investment in equitable infrastructure, structured capacity building aligned with UNESCO’s Digital Literacy Global Framework and ICT (Information and Communication Technology) Competency Framework for Teachers, and explicit attention to ethics and inclusion. Future research should adopt longitudinal and comparative designs to trace the impact on educator identity, collaboration, and learner outcomes.